An improved mechanized pepper [Piper nigrum] thresher - Jusuh, Ahmad; Bong, Choon Fah Joseph; Saad, M. S. (1985)
An improved mechanized pepper thresher was designed, at the Universiti Pertanian Malaysia Cawangan Sarawak, to carry out three main functions: to detach berries from the spikes, to separate detached berries from the empty spikes or stalks, and to separate large berries ( 5mm diameter) for white pepper production. Three stages of tests: threshing efficiency, sieving effectiveness, and threshing and sieving combination tests were conducted to obtain the best drum rotating and sieve vibration speeds. The best combination speed was 800 and 320 rpm for drum and sieve respectively. At these rpm, the thresher was capable of threshing 250 kg/hour green berries giving 99.9% threshing efficiency with less than 10% damaged berries, and effective sieving.